Anesthetic management in a super obese parturient undergoing elective caesarean section: A case report - Kavita Jain; Beena Thada; Surendra K Sethi (Wolters Kluwer Medknow Publications, 2019)
Obesity has become a global epidemic nowadays with a considerable rise in prevalence among reproductive age group. In obese parturients, the perinatal and maternal morbidity are more common, so it is more likely to plan for elective caesarean section. Morbidly obese parturients along with physiological and pharmacological variations pose significant challenges such as patient positioning, difficult intravenous cannulation, anticipated difficult airway, risk of aspiration, associated comorbidities, postoperative ventilatory support, and risk of thromboembolism under general anesthesia. Hence, regional anesthesia is the preferred technique; however, it can also be challenging with factors such as identification of midline and epidural space, number of attempts, accidental dural puncture, and correct placement of catheter. Here, we report a case of a 34-year-old super obese parturient with gestational hypertension and hypothyroidism who underwent elective caesarean section under combined spinal epidural anesthesia.